Enhancing Microgrid Stability with D-STATCOM and Battery-Based Storage - Maithem Hassen Kareem Almousawi; Dr. Mohsen saniei; Dr. mortazavi (Migration Letters, 2023)
Microgrids have gained significant attention as a promising solution for achieving sustainable and resilient energy systems. However, the integration of renewable energy sources (RES) into microgrids introduces challenges related to transient stability. This paper proposes a comprehensive approach to enhance transient stability and improve renewable energy integration in microgrids using a combination of a Distribution Static Compensator (D-STATCOM) and a battery-based storage system. The D-STATCOM provides reactive power compensation and voltage regulation capabilities, while the battery-based storage system offers energy storage and dispatchability. The synergistic operation of these two components addresses the intermittent nature of renewable energy sources and improves the overall performance of the microgrid during transient events. The effectiveness of the proposed approach is evaluated through simulation studies using a representative microgrid model. The suggested MG was designed and simulated in MATLAB. The MG has also been shown to function reliably across a wide range of environmental and loading situations. All use scenarios are covered by the suggested design.